PENGARUH PEMBERDAYAAN, LOCUS OF CONTROL TERHADAP KINERJA KARYAWAN DENGAN DIMEDIASI KEPUASAN KERJA. (Studi Pada PT. Telekomunikasi Indonesia Tbk, Regional Jawa Timur, Kantor Area Sidoarjo dan ARNET SBT) - Arif Reza Fahmi Munawar, 11.42.02.0012 (Students Journal of Economic and Management, 2013)
This research takes an object of research at employees working in PT Telecommunications Indonesia Tbk, East Java Regional, especially Sidoarjo area and ARNET SBT A Total of 116 respondents. The company would want to be a good employee performance, thus the need to increase the job satisfaction of employees for job satisfaction greatly affect the performance of the employees. In addition the company needs to implement a program of empowerment and saw locus of control each of its employees, for empowerment in an organization or company to be an important phenomenon to support the performance of an employee. Test results contained a positive influence between empowerment on job satisfaction, contained partial positive influence between locus of control on job satisfaction, there is no partial influence of empowerment on employee performance, contained partial positive influence between locus of control on employee performance, contained partial positive influence between job satisfaction on employee performance. Mediation results showed that job satisfaction mediates the effect of empowerment on employee performance and job satisfaction did not mediate the effect of locus of control on employee performance. Keyword :       Empowerment, Locus of control, Job satisfaction and Employee performance